CEO turnover and corporate innovation: What can we learn from Chinese listed companies - Sun, Shujun; Jiang, Haiwei (Frontiers in Psychology, 2022)
Using data of China’s listed companies from 2000 to 2016, this paper employs the staggered difference-in-difference model to study the impact of CEO turnover on corporate innovation. First, listed companies with CEO turnover experienced an average increase of 9.5% in the quantity of innovation and 8.9% in innovation quality after the change. Second, CEO turnover plays a more significant role in promoting innovation for listed firms with CEO duality, high financial constraints, and in high-tech industries. Third, CEO turnover affects corporate innovation by driving top management team reorganization and promoting R&D input.